Quantitative study of embodied carbon in the housing development project. - Ting, Jordan Chao Jien (2024)

(untitled)
In Malaysia, the carbon emission from construction sector is not emphasized significantly. However, the carbon emission from the buildings can take up to 39 % of overall global energy-related carbon emissions and contributed by a broad range of stakeholders. Thus, it could be difficult to track and control the carbon footprint in buildings. This study aims to provide a comprehensive understanding on the quantitative study on indirect energy-related emissions, so called embodied carbon in housing development projects using Life Cycle Assessment (LCA) method, and present appropriate solutions for decreasing the embodied carbon. This research is conducted based on a gross floor area with 92.903 m2 of residential building project in Malaysia. It addresses the challenges faced by Malaysian construction industry in embodied carbon emissions. The embodied carbon within cradle-to-site of the studied building was calculated and reported instead of on-site waste generation. The result shows that a single unit of residential buildings accounted for 68.60 tCO2e (0.738 tCO2e/m2 ). Embodied carbon released from the material manufacture was consisted by steel (38.12 %), bricks (15.26 %), and concrete (14.16 %). The findings declare that the embodied carbon could be lowered down using low carbon concrete and material minimization through recycling and reuse. In addition, the local material sourcing within distances of 200 km could reduce 11 % of the EC from the material transportation. However, government policy is the crucial key to adopt carbon assessment across the construction industry and make the data collection easier for implementing carbon reduction strategies effectively. The outcome of this study can be used as the reference for Malaysia’s construction companies to start an early embodied carbon assessment. The developed LCA analysis framework may improve residential buildings’ embodied carbon assessment.